FRI0210 Poor immunization with hepatitis B vaccination in patients with granulomatosis with poliangiitis (wegener's) and more favorable antibody response in females. (23rd January 2014) - Kara, E.; Erer, B.; Artim Esen, B.; Omma, A.; Sahinkaya, Y.; Kanitez, N.; Gul, A.; Inanc, M.; Aral, O.; Ocal, L.; Kamali, S.
Abstract : Background: Hepatitis B (HepB) is an endemic infection in Turkey, with an intermediate risk rate (2-7%). HepB vaccination has long been advised in high risk population, especially in endemic areas. Granulomatosis with poliangiitis (GPA) patients can be considered at high risk due to the requirement of frequent diagnostic and therapeutic upper and lower airway procedures. Objectives: We aimed to investigate antibody response and safety profile of HepB vaccination in patients with GPA. Methods: Sixty GPA patients who have been regularly followed-up since 1994 were included into the study. They were screened for HepB virus infection by HbsAg, anti-Hbs, anti-HbcIgG serology. Active patients according to BVAS2003 (BVAS≥1) were excluded from the study. The patients who had negative for all 3 tests and inactive disease were involved into the vaccination programme. All but 2 patients had systemic GPA. Two GPA patients receiving moderate dose (≥7, 5 mg/d) of glucocorticoid (GC) scheduled to a standardized tapering protocol and meeting remission criteria were also allowed to the study. Recombinant HepB vaccination was applied by im route for each patient at 0, 1th and 6th months. The clinical, laboratory and treatment findings, BVAS scores and adverse events were noted into a predefined protocol and adverse event form at the study visits and ≥1 month after each dose of vaccination. Cumulative doses of immunosuppressive (IS) drugs before 6 months and during the vaccination period were separately calculated. HbsAg antibody response was tested by ELISA method. Positive results were accepted for serum antibody titers >10 IU/ml. Mann Whitney U test was used to compare the demograhic characteristics and the doses of IS between the responders and nonresponders. Results: Twenty (12 male, 8 female) GPA patients aged between 22-68 years were found to be eligible for vaccination programme. The patients were on AZA (n=11), MTX (n=3), CYC (n=1), LEF (n=2), MMF (n=1) and RIT (n=2) during the study period. Cumulative GC doses were 1.1±1 (0.3-2) and CYC doses were 0.7±1.8 (0-6), before vaccination. Positive antibody response was detected only in 45% of cohort (>100 IU/ml in 20%). There were no relationship between the antibody response and age, disease duration and IS doses. The antibody response was significantly more frequent in female patients compared to males (75% vs 25%, p=0, 02). No significant difference in IS treatment and doses was observed regarding the gender of patients. Mild injection site reactions (10%), myalgia (5%) and fever (5%) were the adverse event related to vaccination. Flare was not observed in any patient during the vaccination period. Conclusions: This is the first report on the HepB vaccination in GPA patients. Antibody response to HepB vaccination has been found in lower rates (45%) than the expected in healthy controls (>90%) which may be resulting from intense immunosuppressive treatments for the systemic involvement of this GPA cohort. Female GPA patients have had a notably higher response to HepB vaccination similar to the immunization results in healthy women. The higher or booster doses might be needed for GPA patients, especially for males. Disclosure of Interest: None Declared